Modifying the surface of peptide nanofibers utilizing a thiol‐thioester exchange. Issue 2 (29th April 2020) - Haddad, Ramiz; Ferraro, Elizabeth; Halmans, Ashley; Smith‐Carpenter, Jillian E.
Abstract: Herein, we report on the incorporation of a dithioester modification to a self‐assembling peptide and characterize a thiol‐thioester exchange on the nanofiber's surface with respect to amount of soluble exogenous thiol present and pH of the reaction. The ratios of all peptide species throughout the exchange reaction were reproducibly monitored by matrix‐assisted laser desorption ionization time‐of‐flight (MALDI‐TOF) mass spectrometry, highlighting the utility of MALDI to characterize heterogeneous and dynamic supramolecular systems. The tuneable revealing of thiols through a dynamic covalent chemical reaction presents a new strategy for labeling supramolecular surfaces. This strategy of combining reversible peptide self‐assembly and dynamic covalent chemistry opens another route for the post‐assembly modification of amyloid‐based supramolecular structures and the design of functional biomaterials. Abstract :